2020
DOI: 10.17358/ijbe.6.1.66
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Personality, Self-Efficacy, and Locus of Control on The Success of Javanese Female Merchants In Surabaya

Abstract: The study aimed to examine the effect of personality on self-efficacy, locus of control, and the success of Javanese female merchants in the modern market, Surabaya, Indonesia. Questionnaire was used as a research instrument in this study. This study involved 100 Javanese female merchants as respondents. The samples were collected through a non-probability sampling technique. The data were analyzed based on Partial Least Square analysis using Smart PLS software. The findings of this study indicated that all fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…Thus, it can be concluded that the better the Efficacy, the more Entrepreneurial Intention will increase. This is because self-efficacy is a predictor that contributes well to the formation of business interests and business development (Oyeku, Oduyoye, Elemo, Karimu, & Akindoju A F, 2014), therefore, someone with self-efficacy, will be motivated to do entrepreneurship, this is in line with the opinion (Laily & Wahyuni, 2020)where good self-efficacy will encourage someone to develop a business and be professionally responsible. Drnovšek et al, (2010) also explained that this encouragement could be in the form of a willingness to understand conditions, situations, and information about the business to be developed to achieve a professional business.…”
Section: Discussionmentioning
confidence: 69%
“…Thus, it can be concluded that the better the Efficacy, the more Entrepreneurial Intention will increase. This is because self-efficacy is a predictor that contributes well to the formation of business interests and business development (Oyeku, Oduyoye, Elemo, Karimu, & Akindoju A F, 2014), therefore, someone with self-efficacy, will be motivated to do entrepreneurship, this is in line with the opinion (Laily & Wahyuni, 2020)where good self-efficacy will encourage someone to develop a business and be professionally responsible. Drnovšek et al, (2010) also explained that this encouragement could be in the form of a willingness to understand conditions, situations, and information about the business to be developed to achieve a professional business.…”
Section: Discussionmentioning
confidence: 69%
“…However, personality affects locus of control and even one's success. Study shows that this hold for Javanese female merchants in Surabaya [2]. Which the author thinks the point of view can be extended for all people.…”
Section: Introductionmentioning
confidence: 67%
“…Surat Edaran pemerintah tanggal 18 maret 2020 mengintstruksikan bahwa kegiatan indoor atau outdoor seluruh sektor dibawahnya dilakukan penundaan dengan tujuan mengurangi penyebaran Covid-19, termasuk dalam hal ini sektor pendidikan (Putra and Putri, 2021). Menurut Fauzi dan Khusuma, studi yang ada tentang kesiapan guru sekolah dasar dalam pembelajaran online pada masa pandemi lebih berorientasi pada aspek eksternal guru (Laily and D.Wahyuni, 2020). Sedangkan menurut Korhonen dalam Arif, Munfa'ati and Kalimatusyaroh (2021), salah satu kompetensi guru yang perlu ditingkatkan pada proses pembelajaran di tengah pendemi Covid-19 adalah kompetensi pedagogik.…”
Section: Hasil Dan Pembahasanunclassified